2019
DOI: 10.1111/exd.14011
|View full text |Cite
|
Sign up to set email alerts
|

Is there still a role for UV therapy in itch treatment?

Abstract: Itching is a frequent and greatly distressing symptom related to many skin and systemic diseases. New insights into the pathophysiology of itchy skin and potentially involved mediators have increased the interest in and development of new treatments that specifically act on targets involved in the transmission and perception of itching. Phototherapy has long been known and used as an effective treatment for various kinds of chronic itching. However, despite its well‐known beneficial effects, the mechanisms beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 69 publications
1
16
0
1
Order By: Relevance
“…This may emphasize observations from clinical routine that patients deem conventional itch therapies often unsatisfactory 28,29 and partly explain why they turn to CAM and “other treatments.” The unexpectedly high rating of CAM in our population may also be due to the high proportion of patients with atopic dermatitis, in which frequent use of CAM is well known 30 . In addition to the potent antipruritic effect of light therapy, this modality may also be popular in itch patients because it may have a mood‐enhancing side effect 31,32 . Apart from itch relief, many patients wished that an ideal itch drug would also allow sleep improvement, psychological relaxation, and pain relief.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may emphasize observations from clinical routine that patients deem conventional itch therapies often unsatisfactory 28,29 and partly explain why they turn to CAM and “other treatments.” The unexpectedly high rating of CAM in our population may also be due to the high proportion of patients with atopic dermatitis, in which frequent use of CAM is well known 30 . In addition to the potent antipruritic effect of light therapy, this modality may also be popular in itch patients because it may have a mood‐enhancing side effect 31,32 . Apart from itch relief, many patients wished that an ideal itch drug would also allow sleep improvement, psychological relaxation, and pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…30 In addition to the potent antipruritic effect of light therapy, this modality may also be popular in itch patients because it may have a moodenhancing side effect. 31,32 Apart from itch relief, many patients wished that an ideal itch drug would also allow sleep improvement, psychological relaxation, and pain relief. As standard itch therapies…”
Section: Discussionmentioning
confidence: 99%
“…In one retrospective study, Bulur et al demonstrated elimination of pruritus in 80% of their elderly patients receiving narrowband UV-B treatment for chronic idiopathic pruritus [121]. Known risks of phototherapy include an erythematous sunburn reaction, aging of the skin, increased risk for non-melanoma skin cancer, and a paradoxical induction of itch if phototherapy doses are too high [122]. Despite concerns of potential adverse effects due to age-related barrier and immune function, the minimal dose to cause erythema has not been shown to differ significantly between older and younger populations and adverse effects are reported at comparable rates [123, 124].…”
Section: Systemic Medications and Precautions In The Elderlymentioning
confidence: 99%
“…In contrast to psoriasis, 1‐25 atopic dermatitis 26‐47 and pruritus 21,35,48‐70 whose therapeutic landscapes have dramatically changed over the last few years due to many advances in skin research, scleroderma remains a challenge in many aspects.…”
mentioning
confidence: 99%